2011
DOI: 10.1007/s10803-011-1377-8
|View full text |Cite
|
Sign up to set email alerts
|

Taste Identification in Adults with Autism Spectrum Conditions

Abstract: Sensory issues are widely reported in Autism Spectrum Conditions (ASC). Since taste perception is one of the least studied senses in ASC we explored taste identification in adults with ASC (12 males, 11 females) compared to control participants (14 males, 12 females). 'Taste strips' were used to measure taste identification overall, as well as bitter, sour, sweet and salty tastes. Results revealed lower taste scores overall in the ASC group, as well as for bitter, sour and sweet tastes. Salty taste scores did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 30 publications
1
42
1
Order By: Relevance
“…Several studies have proposed neurobiological mechanisms to explain how oral sensory sensitivity may result in food selective behaviors. Tavassoli & Baron-Cohen (2012) reported differences in taste identification as measured using taste strips between adults with ASD and a control group. Bennetto, et al (2007) found that individuals with ASD perceived olfaction and taste stimuli differently than those without ASD; however, there were no differences in detection thresholds using stimuli presented via electrodes on the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proposed neurobiological mechanisms to explain how oral sensory sensitivity may result in food selective behaviors. Tavassoli & Baron-Cohen (2012) reported differences in taste identification as measured using taste strips between adults with ASD and a control group. Bennetto, et al (2007) found that individuals with ASD perceived olfaction and taste stimuli differently than those without ASD; however, there were no differences in detection thresholds using stimuli presented via electrodes on the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, findings for olfactory processing in ASD have been mixed (Bennetto, Kuschner, & Hyman, 2007;Dudova et al, 2011;May et al, 2011;Suzuki, Critchley, Rowe, Howlin, & Murphy, 2003;Tavassoli & Baron-Cohen, 2012), so further investigation is warranted, particularly as unusual adaptation to stimuli has been observed in the visual (Pellicano, Jeffery, Burr, & Rhodes, 2007) and tactile (Tommerdahl, Tannan, Cascio, Baranek, & Whitsel, 2007) domains. Furthermore, some participants described a phenomenon where, once fixated on a strong stimulus, they became unable to consciously process information in the other sensory domains.…”
Section: Discussionmentioning
confidence: 99%
“…Defined as unusual reactions to stimuli, atypical reactivity can be observed as hypersensitivity and/or hyposensitivity, sensory distortions (e.g., inconsistent spatial localization of percepts), and/or sensory blackouts where sound and vision vanish and return. Abnormal reactivity in ASD has been reported for taste [Bennetto, Kuschner, & Hyman, 2007;Tavassoli & Baron-Cohen, 2012], smell [Bennetto et al, 2007;Galle, Courchesne, Mottron, & Frasnelli, 2013], touch [Blakemore et al, 2006;Puts, Wodka, Tommerdahl, Mostofsky, & Edden, 2014], vision [Bryson et al, 1990;Grandin, 2009;Mottron et al, 2007;Simmons et al, 2009;Trachtman, 2008;Wainwright & Bryson, 1996;Wainwright-Sharp & Bryson, 1993], and hearing [Crane et al, 2009;O'Neill & Jones, 1997;Wiggins, Robins, Bakeman, & Adamson, 2009]. General, unspecified sensory hyperactivity and over-selectivity across all sensory modalities has also been acutely described in people with ASD [Tavassoli, Miller, Schoen, Nielsen, & BaronCohen, 2014].…”
Section: Introductionmentioning
confidence: 99%